Spatial features identification of the population trading service development in Kharkiv region with the use of the univariate statistical analysis - Pavlo Kobylin; Nataliia Dobrovolska; Iryna Skryl; Volodymyr Redin (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The paper describes spatial features identification of the population trading service development in Kharkiv region with the use of the univariate statistical analysis. Kharkiv region as one of the most developed regions of Ukraine is characterized by a high degree of monocentric regional development. The univariate statistical analysis was chosen in order to assess this degree. Univariate statistical analysis is a type of statistical analysis used to characterize the distribution of a single variable. The following parameters of descriptive statistics were selected as characteristics of the values distribution: median, mode, mean, variance, standard deviation, coefficient of variation, coefficient of skewness, and coefficient of kurtosis. Such indicators are characterized in the paper: a number of population, a number of trade enterprises, a number of restaurant facilities in the settlements of the region. The normal distribution of a random variable was taken for the ideal distribution of the indicators values. The distribution is normal if the median, mode and mean are equal to each other, the coefficients of skewness and kurtosis should equal 0. According to the results of a univariate statistical analysis, it was determined that the distribution of the above mentioned in-dicators don’t correspond to a normal distribution, it is extremely uneven, which confirms the monocentricity of regional development in Kharkiv region. Distribution of indicators of the number of population, trade enterprises, and restaurant facilities is similar to each other, which indicates conditionality of the existing network of trade enterprises, restaurant facilities to the population in settlements. The analysis of the descriptive statistics parameters in the context of the newly formed administrative districts of Kharkiv region was carried out and it was found that any district isn’t characterized by the normal distribution of the above indicators, however, the most distant from the normal distribution is Kharkiv district, the most closed are Bogodukhivsky, Chuhuivsky, Krasnohradsky districts.